2008
DOI: 10.1038/pcan.2008.14
|View full text |Cite
|
Sign up to set email alerts
|

Probability of finding T1a and T1b (Incidental) prostate cancer during TURP has decreased in the PSA era

Abstract: The purpose of this study is to assess the likelihood of detecting stage T1a and T1b cancer in transurethral prostatectomy specimens during the PSA era. Comparison was made of transurethral resection of prostate (TURP) cohorts in the pre-PSA era (1986)(1987) and the PSA era (1994)(1995)(1996)(1997)(1998)(1999)(2000), excluding patients with known PCa. A total of 228 men without a known history of prostate cancer underwent TURP during the pre-PSA era time frame and 501 underwent the procedure during the PSA era… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 17 publications
1
56
0
2
Order By: Relevance
“…9 More recently, Jones et al found a decrease of incidental prostate cancer from 14.9% to 5.2% (pre versus post PSA era) in over 700 patients. 10 They saw significant decreases in both pT1a and pT1b incidental prostate cancer (4.4% to 2.2% and 10.5% to 2.8%, respectively) between the pre-PSA and the PSA era. Other possible reasons for the reduction in incidental prostate cancer include the decreased rate of surgical management of BPH due to increased use of medical therapy as well as an increased use of ablative therapies, which do not always provide tissue for pathologic analysis in patients who ultimately require surgical management of their BPH.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…9 More recently, Jones et al found a decrease of incidental prostate cancer from 14.9% to 5.2% (pre versus post PSA era) in over 700 patients. 10 They saw significant decreases in both pT1a and pT1b incidental prostate cancer (4.4% to 2.2% and 10.5% to 2.8%, respectively) between the pre-PSA and the PSA era. Other possible reasons for the reduction in incidental prostate cancer include the decreased rate of surgical management of BPH due to increased use of medical therapy as well as an increased use of ablative therapies, which do not always provide tissue for pathologic analysis in patients who ultimately require surgical management of their BPH.…”
Section: Discussionmentioning
confidence: 95%
“…Prior to our findings, detection rates in the PSA era ranged from 4.8% to 16.7%. [8][9][10][11][13][14][15] Dellavedova et al found an incidental prostate cancer detection rate of 7% when they reviewed 100 patients who underwent bipolar TURP. 11 Six patients had Gleason grade 3+3 pT1a disease and one patient had Gleason grade 3+4 pT1b disease.…”
Section: 12mentioning
confidence: 99%
“…The TNM classification distinguishes stages T1a (<5% of the resected tissue) and T1b (>5% of the resected tissue) disease [1]. The incidence of IPCa has been reported to be 5.2-6.4% [2,3], but no unequivocal statement regarding the appropriate treatment has thus far been made, because only studies with small numbers of cases are currently available. For patients with IPCa and a low Gleason score (≤6) there are good reasons for proceeding with non-invasive protocols, as several studies have shown that cancer-specific survival times are approximately equal to normal life expectancy [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer has been found incidentally in TURP specimens without prior diagnosis in 5% to 13% of patients. [1][2][3] According to the TNM staging system, incidental tumour in less than 5% of resected prostate tissue is subclassified in clinical stage T1a; tumour found in more than 5% of resected tissue is subclassified as T1b. 4 Although most of the incidental prostate cancers are considered clinically insignificant, recent studies have suggested that in some of them, the clinical course becomes more unfavourable.…”
Section: Introductionmentioning
confidence: 99%